Forgotten academic modernism in the reconstruction of downtown Le Havre by Auguste Perret - Szumigała, Paweł Piotr; Szumigała, Karolina Olenia (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
This paper attempts to present historical architectural and urban structures realized in the style of academic modernism on the example of the reconstruction of Le Havre. The reconstruction of Le Havre is a full-scale depiction of an urban structure in a unified modernist style, combining academic classicism and modernity. After years of experience in urban planning, the image of the reconstruction of Le Havre after the destruction of war is, in the context of contemporary urban planning concepts, an example of holistic urban thinking about urban space.